Staufen2-mediated RNA recognition and localization requires combinatorial action of multiple domains - Heber, Simone; Gáspár, Imre; Tants, Jack-Niklas; Günther, Johannes; Fernandez Moya, Sandra Maria; Janowski, Robert; Ephrussi, Anne; Sattler,Michael; Niessing, Diessing (Springer Nature, 2019)
Throughout metazoans, Staufen (Stau) proteins are core factors of mRNA localization particles. They consist of three to four double-stranded RNA binding domains (dsRBDs) and a C-terminal dsRBD-like domain. Mouse Staufen2 (mStau2)-like Drosophila Stau (dmStau) contains four dsRBDs. Existing data suggest that only dsRBDs 3–4 are necessary and sufficient for mRNA binding. Here, we show that dsRBDs 1 and 2 of mStau2 bind RNA with similar affinities and kinetics as dsRBDs 3 and 4. While RNA binding by these tandem domains is transient, all four dsRBDs recognize their target RNAs with high stability. Rescue experiments in Drosophila oocytes demonstrate that mStau2 partially rescues dmStau-dependent mRNA localization. In contrast, a rescue with mStau2 bearing RNA-binding mutations in dsRBD1–2 fails, confirming the physiological relevance of our findings. In summary, our data show that the dsRBDs 1–2 play essential roles in the mRNA recognition and function of Stau-family proteins of different species.
Keywords: Interacciones ARN-proteína; RNA; RNA-binding proteins; Staufen; RNA structure; Hairpin; Protein domain